ATTITUDE TOWARDS HANDLING OF EMPTYPACKAGED DRINKING WATER BOTTLE - Vanitha, S. (International Journal of Research -GRANTHAALAYAH, 2016)
Water is one of most essential product for our life. Without water any living beings cannot live for a longer period of time. Water is one of the important top five sources for all. Role of water cannot be measured. Such the vital role is done by water in the body. It gives strength, clear all unnecessary contains from our body, refresh our flesh, and maintain correct temperature and so on. It is very much important that drinking a good water. These days, water is highly polluted due to the industrial growth. Therefore, water is sold in the packet. As it is little difficult to bring water wherever we go, people prefer to buy this packaged water. After drinking the water, people simply throw the packet in the dustbin. It creates the environment pollution problem. Now, green management has very important to protect the world from pollution. It urges the scholar to study about the importance of the packet water and how can be protected our environment from these waste. It also deals with giving suggestion to use packet water without pollute the environment.